The Controversies of Historical-Anthropological Research in the Subculture of Czech Chimney Climbers - Vacek, Přemysl (Dějiny – teorie – kritika, 2025)
Chimney climbing as represented by the Czech Smokestack-climbers Society (Svaz českých komínářů) has existed in our country for more than forty years. Today, it has over a thousand registered followers who contribute to creating a unique subculture with original symbolism, jargon, terminology, and specific practices. This has become an important formative aspect of lifestyle for many fans of this activity. Initially a student prank involving “gratuitous” climbing of the smokestacks, the activity of the chimney climbers has gradually expanded to increase the visibility of the value of industrial monuments and to create records of industrial objects shared in their own extensive electronic database. This study aims to provide basic information on selected aspects of the unique Czech phenomenon of chimney climbing. It focuses on the controversial elements that are part of the chimney climbers' activities, such as the parody of official structures, the legal controversy of their actions or the specific perception of their own safety. It also examines the implications of these controversies for research and its methodology. Organized chimney-climbing is framed in the socio-political context, within which it emerged and has evolved over time.